A new polymeric thin film by using electropolymerization: thin film of poly(phenazine-salen) obtained from 2,2'-[1,2-ethanediylbis(nitrilomethylidyne)] -bis[4-amino-phenol] - Martin, Cibely S. [UNESP]; Olean-Oliveira, André [UNESP]; Teixeira, Marcos F.S. [UNESP] (My University, 2020)
In the last years, the study of the formation of a polymer containing multidentate Schiff-base ligand as subunits has been performed. In general, the electropolymerization occurs through the interaction between the phenyl rings and metallic centers. However, in this paper, we proposed a new polymeric thin film formation from 2,2'-[1,2-ethanediylbis(nitrilomethylidyne)]bis[4-amino-phenol] obtained by electropolymerization. The electropolymerization mechanism for poly(phenazine-salen) formation was based on the carbon-nitrogen coupling. The effect of experimental parameters such as scan rate, applied potential range, supporting electrolyte, and solvent type on the electropolymerization process was also evaluated. The poly(phenazine-salen) film was characterized by cyclic voltammetry and electrochemical impedance spectroscopy in an inert supporting electrolyte showing a redox couple ascribed to pyrazine moieties. The Mott-Schottky plot of the electropolymerized material indicated that the polymer is an n-type semiconductor. The results indicate a polymeric formation controlled by the electropolymerization parameters and the electrochemical behavior tuned by the ions insertion/extraction from supporting electrolyte.
Keywords: Electropolymerization; New thin film; Poly(phenazine-salen); Polymer film